Epstein-Barr virus associated oesophageal ulcers in AIDS. Issue 11 (November 1990) - Kitchen, V S; Helbert, M; Francis, N D; Logan, R P; Lewis, F A; Boylston, A W; Pinching, A J; Harris, J R
Abstract : Epstein-Barr virus (EBV) associated ulceration has not previously been included in the differential diagnosis of oesophageal ulcers in AIDS. We report five cases of oesophageal ulceration in homosexual men with advanced human immunodeficiency virus infection in whom this was considered to be the most likely cause. DNA in situ hybridisation studies showed EBV in biopsy material from three of four patients with oesophageal ulcers and in none of three controls. Of other viruses studied, only human papillomavirus was present, and this was found in both patients and control subjects. These findings support the hypothesis that EBV is an aetiological factor in some cases of AIDS-associated oesophageal ulceration.